2013
DOI: 10.1002/jid.2929
|View full text |Cite|
|
Sign up to set email alerts
|

Rethinking Acp‐eu Relations After Cotonou: Tensions, Contradictions, Prospects

Abstract: This Policy Arena has two main objectives. First, it seeks to unravel how the partnership between the European Union (EU) and the African, Caribbean and Pacific (ACP) Group has evolved since the adoption of the Cotonou Agreement in 2000, including its 2005 and 2010 reviews and the implementation of its three key pillars (development cooperation, trade and political dialogue). Second, it explores the prospects of EU‐ACP relations in the medium to long term. In particular, it discusses whether the ACP‐EU coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…This article has shed light on the European Commission's proposal recommending renewal of the EU-ACP Agreement along two interlinked dimensions: a general part applicable to all ACP countries and three distinct compacts for countries in Africa, the Caribbean and the Pacific. Preservation of the EU-ACP cooperation model, albeit through a hybrid format, was controversial because of its patchy record in terms of human development and economic growth, the opposition of various EU member states, and the existence of allegedly more legitimate and effective frameworks for engaging with ACP countries and addressing global challenges (Carbone 2013b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has shed light on the European Commission's proposal recommending renewal of the EU-ACP Agreement along two interlinked dimensions: a general part applicable to all ACP countries and three distinct compacts for countries in Africa, the Caribbean and the Pacific. Preservation of the EU-ACP cooperation model, albeit through a hybrid format, was controversial because of its patchy record in terms of human development and economic growth, the opposition of various EU member states, and the existence of allegedly more legitimate and effective frameworks for engaging with ACP countries and addressing global challenges (Carbone 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…A more general analysis of the evolution of EU-ACP relations reveals that policy outcomes are often the result of the convergence of the preferences of a few EU member states, with either France or the United Kingdom, or both, always playing a leading role. Still, the role of the European Commission should not be overlooked, as on various occasions it has appeared to promote continuity more than change (Holland 2002;Babarinde and Faber 2005;Carbone 2013b).…”
Section: Towards a New Eu-acp Agreement After 2020mentioning
confidence: 99%
“…However, The abolishing of such preference was seen as primarily in the interest of the EU [9]. Nonetheless, the EU continued to use the language of partnership.…”
Section: The Basis Of Bilateral or Multilateral Development Relationsmentioning
confidence: 99%
“…Unsurprisingly, the relevance of the Cotonou Agreement, in the run-up to its third review scheduled to be concluded by 2015 and its expiration in 2020, has been questioned not only in Europe but also in various ACP countries(Carbone 2013c).…”
mentioning
confidence: 99%